PFKP and GPC6 Variants Were Correlated with Alcohol-Induced Femoral Head Necrosis Risk in the Chinese Han Population - Liu C; Liu X; Li X (Dove Medical Press, 2022)
Chang Liu,1,* Xuan Liu,2,* Xiaolin Li2 1Emergency Department, The Second Hospital of Tangshan, Tangshan, 063000, People's Republic of China; 2The Fourth Department of Orthopaedics, Tangshan Hongqiao Orthopaedic Hospital, Tangshan, 064100, People's Republic of China*These authors contributed equally to this workCorrespondence: Chang Liu, Emergency Department, The Second Hospital of Tangshan, #21, Jianshe North Road, North District, Tangshan City, Hebei, 063000, People's Republic of China, Tel +86-18633328305, Email liuchang991204@163.comBackground: Osteonecrosis of the femoral head (ONFH) is a common joint disease caused by excessive drinking, genetic factors, etc. The purpose of this study was to investigate the association between PFKP and GPC6 variants and alcohol-induced ONFH (AIONFH) risk in the Chinese Han population.Methods: This study genotyped 9 selected single nucleotide polymorphisms (SNPs) in 402 males by Agena MassARRAY Assay. By calculating odds ratios (ORs) and 95% confidence intervals (CIs), we assessed the effect of gene polymorphisms on AIONFH occurrence. False-positive report probability (FPRP) analysis and power were also used to evaluate the significant results. Multifactor dimensionality reduction (MDR) software was also utilized to predict the association between the selected SNPs and AIONFH risk.Results: The overall analysis showed that PFKP rs10903966 and GPC6 rs7320969 were correlated with AIONFH risk. GPC6 rs4773724 was associated with a reduced risk of AIONFH, while individuals with GPC6 rs9523981 CC genotype had a higher risk of AIONFH than individuals with the other genotypes among people under 42 years old. Based on stratified analysis of necrotic sites, rs7320969 was related to a decreased risk of AIONFH, while rs10903966 and rs9523981 were related to an increased risk of AIONFH. In addition, rs1008993 and rs7320969 were observed to be linked to AIONFH risk in patients at different clinical stages. Meanwhile, there were significant differences in TC, TG, platelet, ApoA1 and ApoB levels among subjects with different genotypes of rs1008993, rs9523981, rs7320969 and rs59624626. The results of MDR showed that rs11251720 and rs7320969 may play a synergistic role in predicting the risk of AIONFH.Conclusion: PFKP rs10903966 and GPC6 rs9523981 were associated with an increased risk of AIONFH, while GPC6 (rs7320969 and rs4773724) were correlated with a decreased risk of AIONFH. This result will need further experiments to verify.Keywords: osteonecrosis of the femoral head, ATP-dependent 6-phosphofructokinase, glypican 6, polymorphism